2001
DOI: 10.1890/0012-9658(2001)082[1799:algiro]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Latitudinal Gradient in Recruitment of Intertidal Invertebrates in the Northeast Pacific Ocean

Abstract: Rates of propagule supply can be important determinants of spatial and temporal patterns in community structure. In the northeast Pacific Ocean, large‐scale differences in the structure of intertidal invertebrate communities have been attributed to a latitudinal gradient in recruitment in this region. To determine whether such a gradient exists, recruitment of intertidal barnacles and mussels was monitored at 17 sites across this region in 1996 and 1997. A latitudinal gradient in recruitment was detected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
263
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 287 publications
(287 citation statements)
references
References 59 publications
18
263
3
1
Order By: Relevance
“…In coastal ecosystems, large-scale biological patterns have mostly been studied in relation to environmental variability over short temporal scales (Connolly et al 2001). The results presented here suggest that species interactions such as competition and facilitation can scale up through larval dispersal and lead to large-scale spatio-temporal patterns with specific scaling properties (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…In coastal ecosystems, large-scale biological patterns have mostly been studied in relation to environmental variability over short temporal scales (Connolly et al 2001). The results presented here suggest that species interactions such as competition and facilitation can scale up through larval dispersal and lead to large-scale spatio-temporal patterns with specific scaling properties (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…The west coast of North America is an eastern boundary ecosystem where spatial and temporal variation in larval recruitment can be influenced by the dynamics of wind-driven coastal upwelling (Parrish et al, 1981;Mooers and Robinson, 1984;Norton, 1987;Graham et al, 1992;Wing et al, 1995b;Connolly et al, 2001). Equatorward wind stress displaces coastal surface waters offshore via Ekman transport, which are replaced by colder, nutrient rich, subsurface waters (Huyer, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Relaxation or reversals in wind stress can lead to downwelling conditions where the warmer offshore surface waters and the coastal fronts are advected back onshore, delivering entrained larval organisms to the nearshore benthic habitat (Roughgarden et al, 1988;Farrell et al, 1991). Several studies have shown that variable recruitment of coastal organisms is related to upwelling dynamics in the California region (Parrish et al, 1981;Hollowed et al, 1987;Ebert and Russell, 1988;Roughgarden et al, 1988;Larson et al, 1994;Wing et al, 1995b;Connolly et al, 2001;Broitman et al, 2005;Laidig et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased upwelling can have two effects: reduced nutrient supply to phytoplankton (8) and reduced offshore transport of phytoplankton and planktonic fish and invertebrate larvae that are crucial for replenishing coastal populations (9). Nutrient and phytoplankton reductions may decrease zooplankton (including larvae) survival, and thus decrease recruitment rates of planktotrophic larvae.…”
mentioning
confidence: 99%